RESPON PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS TANAMAN JAGUNG (Zea mays L.) TERHADAP PEMBERIAN PUPUK N DAN P - Sehat Bahrin Padang; Mbue Kata Bangun; Lollie Agustina P Putri (Jurnal Agroekoteknologi, 2013)
Sehat Bahrin Padang : The Growth and Production Response of Some Maize VarietiesThrough by N and P Application. Supervised by Ir. Mbue Kata Bangun, MP andDr. Ir. Lollie Agustina P. Putri, M.Si. The use of Central Composite Rotatable Design (CCRD) wasto determine the response surface produce at maize not yet a lot of checked, for that a research hadbeen conducted in UPT BBI Tanjung Selamat, Regency of Deli Serdang, Province of NorthSumatra at ± 25 m above sea level, in May 2012 - August 2012 using randomized block design oftwo factors, the factors are varieties (Bisma and SHS-4) and NP fertilize (NP dose prescribed ofCCRD). Parameters measured were: plant height, the number of leaf, the number of leaf above cob,flowering age, harvesting age, cob lenght, cob diameter, wight 100 seeds, production of dry seeds.The results showed that the varieties significantly different in maize height, the number of leafs,flowering age, wight 100 seeds and dry seeds production. Fertilize sigificantly affects flowering ageand harvesting age. Interaction factor significantly affects flowering age and the number of leafabove cob.Keyword : maize, N and P fertilizer, varieties